PERKEMBANGAN PENDIDIKAN SUKU TALANG MAMAK DESA DURIAN CACAR KECAMATAN RAKIT KULIM KABUPATEN INDRAGIRI HULU TAHUN 2005-2015 - Siti Hasanah; Isjoni Isjoni; Asril Asril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Talang Mamak tribe is belong to old malay (proto melayu) it is the original tribe from Indragiri Hulu according to some oral version derived from Datuk Perpatih Nan Sebatang generation who is one of the pagaruyung royal swordsman. Talang Mamak tribe has two groups the first is Talang Mamak tribe Limau River that settles around the River Limau and River Batang Cenaku. Second, the group of Talang Mamak Gansal River and Root River in the mountain environment of Bukit Tiga Puluh. This study aims to determine: (1) development of Talang Mamak tribe education before 2005. (2) development of Talang Mamak tribe education year 2005-2015. (3) community perception of Talang Mamak tribe to education. This research used descriptive method with qualitative approach with data collection techniques such as conservation, interview, documentation, questionnaire and bibliography. The results of this study showed (1) the development of education tribal talang mamak before 1999 only has 1 unit of school with 1 educator who doubles as principal (2). The development of education tribe talang mamak year 2005-2015 experienced a good development, this is evidenced by the number of educators who increased and the number of students more and more. (3). The perception of gamelan mamak tribe to education is very low due to the distance between the house and the relative school, the state of the damaged transportation road, the parents' understanding about the importance of education is still low, as well as the economic and cultural stability of the culture.Keywords : Development. Education of Talang Mamak Tribe.